Monoamine oxidase A polymorphism moderates stability of attention problems and susceptibility to life stress during adolescence - Zohsel, Katrin; Schmidt, Martin H.; Brandeis, Daniel; Banaschewski, Tobias; Laucht, Manfred (Genes, brain and behavior, 2015)
Attention problems affect a substantial number of children and adolescents and are predictive of academic underachievement and lower global adaptive functioning. Considerable variability has been observed with regard to the individual development of attention problems over time. In particular, the period of adolescence is characterized by substantial maturation of executive functioning including attentional processing, with the influence of genetic and environmental factors on individual trajectories not yet well understood. In the present investigation, we evaluated whether the monoamine oxidase A functional promoter polymorphism, MAOA-LPR, plays a role in determining continuity of parent-rated attention problems during adolescence. At the same time, a potential effect of severe life events (SLEs) was taken into account. A multi-group path analysis was used in a sample of 234 adolescents (149 males, 85 females) who took part in an epidemiological cohort study at the ages of 11 and 15 years. Attention problems during early adolescence were found to be a strong predictor of attention problems in middle adolescence. However, in carriers of the MAOA-LPR low-activity variant (MAOA-L), stability was found to be significantly higher than in carriers of the high-activity variant (MAOA-H). Additionally, only in MAOA-L carriers did SLEs during adolescence significantly impact on attention problems at the age of 15 years, implying a possible gene × environment interaction. To conclude, we found evidence that attention problems during adolescence in carriers of the MAOA-L allele are particularly stable and malleable to life stressors. The present results underline the usefulness of applying a more dynamic GxE perspective.
Gesehen am 24.01.2018